PERBANDINGAN MEDIA AUDIOVISUAL DAN CERAMAH TERHADAP SIKAP SISWA TENTANG PENTINGNYA KONSUMSI SAYUR DAN BUAH - Mona Hastuti; Kintoko Rochadi; Etti Sudaryati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
The importance of consuming fruit and vegetables is commonly neglected by the Indonesian people. Only 6.4% of adolescents at the age of 10-14 consume fruit and vegetables about 5 portions or more per day while the remaining 93.6% fewer than 5 portions. It is probably caused by their lack of knowledge and negative attitude toward it so that health promotion, using audiovisual, is needed. The research method used quasi experimental method with group pretest-posttest design. It was conducted at SMPIT AL Musabbihin and  Namira Medan. The population was 58 students consisted of 28 at SMPIT Al Musabbihin and 30at SMPIT Namira. The data were analyzed by using univariate and bivariate analysis with paired-sample t-test at significance level of 95% (α=0.05).The result of statistic test showed that there was significant difference in attitude between the students at SMPIT Al Musabbihin and SMPIT Namira about the importance of consuming fruit and vegetables.The conclusion of the research is that audio visual media is more effective to change students' attitudes become more positive about the importance of vegetable and fruit consumption in SMPIT Al Musabbihin and lecturer method is effective at SMPIT Namira Medan.